Analysis of the legal nature of the tithe from the contract law perspective (Revista da Faculdade de Direito, Universidade de São Paulo, 2023)
Tithe is a long-standing historical figure, present in the social, cultural and religious imagination of Brazilian society. However, in contemporary times, several cases of people who destined part of their patrimony to religious institutions and regretted after, are taken to the Judiciary, which in turn does not have a pacified understanding of the subject. Therefore, this paper seeks to analyze the nature of the tithe from the Contract Law perspective as a donation contract, exploring the requirements of article 538 of the Civil Code, the current case law, the scholar’s opinion and the social, economic and religious aspects on the subject. It is concluded, then, that the tithe can be considered not only a moral and religious duty but also, under the legal aspect, a donation contract.